Jvla and Vlba Study of the Merging Cool Core Chips 1911+4455 at Z ∼ 0.5 Radio Emission from an Infant Active Galactic Nucleus and from a Rapidly Star-Forming Brightest Cluster Galaxy - Olivares-Sepulveda, V (Institute of Physics, 2025)
Recent studies of galaxy clusters found peculiar cases at the boundary between noncool core and cool core systems. While unusual, these objects can help us understand the evolution of the most massive clusters. We investigated the role of active galactic nucleus (AGN) feedback in the starburst brightest cluster galaxy (BCG) of the merging cool core cluster CHIPS 1911+4455 (z = 0.485). We conducted new multifrequency (0.3-5 GHz) Very Long Baseline Array (VLBA) and Jansky Very Large Array (JVLA) observations of CHIPS 1911+4455 across a wide range of scales (0.01-20 kpc). Our analysis reveals that the AGN in the BCG has recently awakened, showing a compact core with symmetric, ∼30 pc long jets in VLBA data. The onset of the AGN may be linked to the enhanced cooling of the hot gas found in a previous study. At larger scales (10 kpc), faint radio whiskers extending to the south show a striking alignment with star-forming knots and are thus interpreted as synchrotron-emitting regions associated with the starburst BCG. The implied radio star formation rate of 100-155 M⊙ yr−1 agrees with the optical/infrared one (140−190 M⊙ yr−1). Our JVLA and VLBA radio study, informed by previous X-ray/optical/millimeter works, indicates that CHIPS 1911+4455 represents a transitional phase in cluster evolution, where the AGN in the central galaxy has just begun to respond to copious hot gas cooling. © 2025. The Author(s). Published by the American Astronomical Society.